A study on Sociodemographic profile and Goat Production System in the Western Undulating Zone of Odisha - Dr. Parag Acharya; Dr. Kumaresh Behera; Dr. Neela Madhav Patnaik; Dr. Jessy Bagh; Dr. Anand Prakash Singh; Dr. Lenin Kumar Gumpha (The Indian Journal of Animal Sciences, 2026)
This study aims to describe socio-demographic aspects, farming practices and production constraints of goat farmers in the western undulating zone of Odisha state of India comprising Kalahandi and Nuapada districts. Ten goat farmers were chosen from each village to gather pertinent information through field visits employing a pre-validated structured questionnaire for a period of around one year from Januaray 2024 to December 2024. The data was collected from experienced goat farmers who are actively engaged in goat farming for more than ten years (n = 320) through personal face to face interview and participatory rural appraisal tools. The majority of goat farmers (90%) reared the native Kalahandi type of goat. Majority of the respondents 76.56% were male and mostly falling within the 40 – 60 year age group. 33.43% respondents were illiterate, while 61.25% had studied up to 5th grade. The majority of the respondents (85.93%) reported their goats attained sexual maturity between 8-10 months, while most (72.81%) having a service period of 3 months. The study identified key challenges affecting productivity and profitability, including feed shortage & shrinking of browsing area, disease prevalence, limited access to improved breeding males, lack of technical training program and predator attacks. The finding of this study highlights the need for targeted interventions to improve goat production in this region particularly by addressing the identified constraints building on the dominance of native Kalahandi type of goats.